Action observation for sensorimotor learning in surgery. Issue 13 (27th September 2018) - Harris, D. J.; Vine, S. J.; Wilson, M. R.; McGrath, J. S.; LeBel, M.‐E.; Buckingham, G.
Abstract : Background: Acquiring new motor skills to learn complex movements and master the use of a diverse range of instruments is fundamental for developing expertise in surgery. Although aspects of skill development occur through trial and error, watching the performance of another individual (action observation) is an increasingly important adjunct for the acquisition of these complex skills before performing a procedure. The aim of this review was to examine the evidence in support of the use of action observation in surgery. Methods: A narrative review of observational learning for surgical motor skills was undertaken. Searches of PubMed and PsycINFO databases were performed using the terms 'observational learning' OR 'action observation' AND 'motor learning' OR 'skill learning'. Results: Factors such as the structure of physical practice, the skill level of the demonstrator and the use of feedback were all found to be important moderators of the effectiveness of observational learning. In particular, observation of both expert and novice performance, cueing attention to key features of the task, and watching the eye movements of expert surgeons were all found to enhance the effectiveness of observation. It was unclear, however, whether repeated observations were beneficial for skill learning. The evidence suggests that these methods can be employed to enhance surgical training curricula. Conclusion: Observational learning is an effective method for learning surgical skills. An improved understanding of observational learning may further inform the refinement and use of these methods in contemporary surgical training curricula. Abstract : Watching other surgeons helpful